How and why to study mountains: topics and types of research between limits and opportunities - Laura Bonato (EtnoAntropologia)
Field practice in a neighbouring ethnographic context – both culturally and geographically –, of which the researcher is a part, entails specific difficulties, epistemological and practical problems quite different from those faced by classical anthropology. Based on the experience gained in three different projects involving the western Alpine arc over the last decade, we intend to highlight the fact that in some contexts it is appropriate to prefer ‘peripheral’ anthropological research, less localised and based on shorter stays. The research conducted in the Piedmontese highlands, despite their differences in terms of assumptions and concretisation, in fact highlights the predominant thematic strands through which mountains are studied in this area.